2018
DOI: 10.1021/acs.jpclett.8b02440
|View full text |Cite
|
Sign up to set email alerts
|

How Ligand Protonation State Controls Water in Protein–Ligand Binding

Abstract: The role of water in protein-ligand binding has been an intensely studied topic in recent years; however, how ligand protonation state change perturbs water has not been considered. Here we show that water dynamics and interactions can be controlled by the protonation state of ligand using continuous constant pH molecular dynamics simulations of two closely related model systems, β-secretase 1 and 2 (BACE1 and BACE2), in complex with a small-molecule inhibitor. Simulations revealed that, upon binding, the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…In this work, we employed the hybrid-solvent continuous constant pH molecular dynamics (CpHMD) simulations with pH replica-exchange 26,27 to determine the catalytic dyad protonation states of renin and characterize the possibly pHdependent conformational dynamics of the flap. The replicaexchange hybrid-solvent CpHMD method has been previously applied to study several pepsin-like aspartyl proteases BACE I, 28,29 BACE II, 30 and CatD 29 and obtained dyad pK a order in agreement with experiments. These studies and another work that examined also other enzymes, 22 demonstrated that the general base or nucleophile forms more hydrogen bond than the general acid or proton donor and some of the hydrogen bonds are absent in the crystal structure and emerge during proton-coupled conformational sampling.…”
Section: Introductionmentioning
confidence: 68%
“…In this work, we employed the hybrid-solvent continuous constant pH molecular dynamics (CpHMD) simulations with pH replica-exchange 26,27 to determine the catalytic dyad protonation states of renin and characterize the possibly pHdependent conformational dynamics of the flap. The replicaexchange hybrid-solvent CpHMD method has been previously applied to study several pepsin-like aspartyl proteases BACE I, 28,29 BACE II, 30 and CatD 29 and obtained dyad pK a order in agreement with experiments. These studies and another work that examined also other enzymes, 22 demonstrated that the general base or nucleophile forms more hydrogen bond than the general acid or proton donor and some of the hydrogen bonds are absent in the crystal structure and emerge during proton-coupled conformational sampling.…”
Section: Introductionmentioning
confidence: 68%
“…Sometimes, structure-based pK a prediction tools, such as the empirical method Propka 3 and the Poisson-Boltzmann solver based methods APBS-PDB2PQR, 4 H++, 5 and DelPhiPKa, 6 are used to obtain estimates of the protonation states prior to running simulations; however, these tools do not directly account for the dynamic flexibility of the protein, which may lead to incorrect assignment of protonation states. Most importantly, even if the initial assignment is correct, protonation states may change in the course of conformational dynamics, as demonstrated in pH-dependent protein folding, 7,8 protein-ligand binding, [9][10][11] enzyme catalysis, 12 and ion/substrate transport across the membrane. 13,14 One solution to the above problems is to use constant pH molecular dynamics (CpHMD) methods to determine protonation states on the fly during the MD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…CpHMD methods have also been implemented in the popular Amber [8] and GROMACS [64] packages, including GBNeck2-CpHMD [35,28] in Amber and the all-atom CpHMD [18] in GROMACS [64]. Here we focus on the extensively validated [75,22,11,33,79,23,29,30,69] pH replica-exchange hybrid-solvent CpHMD method in CHARMM [73], which has been further developed to enable mechanistic studies of membrane proteins [33].…”
Section: Continuous Constant Ph Molecular Dynamics Methodsmentioning
confidence: 99%